In-Use Stability of SB12 (Eculizumab, Soliris Biosimilar) Diluted in Saline and Dextrose Infusion Solution after an Extended Storage Period - Minji Tak; Hawon Jeong; Jihoon Yun; Jihyun Kim; Soyeon Kim; Yoonsook Lee; Su Jin Park (Adis, Springer Healthcare, 2023)
Abstract Introduction SB12 is a biosimilar to eculizumab reference product [SolirisTM (Soliris is a trademark of Alexion Pharmaceuticals, Inc.)] that acts as a C5 complement protein inhibitor. The infusion stability of in-use (diluted) SB12 outside the conditions stated in the reference product's label is unknown. Objective The objective of this study was to assess the stability of SB12 after extended storage in conditions not claimed in the originator label. Methods Infusion stability was assessed in SB12 samples (diluted in 0.9% NaCl, 0.45% NaCl, and 5% dextrose, final concentration of 5 mg/mL per clinical trial protocol and the reference product's label) kept at 5 ± 3 °C for up to 3 months, then 30 ± 2 °C/65 ± 5% relative humidity (RH) for 72 h. The product was stored in different containers [polyolefin (PO) bags, glass bottles and syringes], and the protocol followed International Conference on Harmonisation (ICH) and European Medicines Agency (EMA) requirements for stability evaluation of biological products. Stability was evaluated using complementary assays, including pH, protein concentration (A280), purity (size exclusion-high-performance liquid chromatography, capillary electrophoresis-sodium dodecyl sulfate, and imaged capillary isoelectric focusing), biological activity (C5 binding and inhibition), and safety (subvisible particles). Results Except for charge variants in SB12 diluted in 5% dextrose, all results met the stability acceptance criteria. There were no major changes in terms of physicochemical stability, biological activity, and subvisible particles. Conclusions The infusion stability of SB12 after extended storage (5 ± 3 °C for up to 3 months, then 30 ± 2 °C/65 ± 5% RH for 72 h) was demonstrated for longer periods and at higher temperatures than what is stated in the EU and US labels of the reference product. The physicochemical properties, biological activity, and subvisible particles of in-use SB12 diluted in 0.9% NaCl and 0.45% NaCl were maintained under the described conditions and for all tested containers. However, instability was observed for the diluted SB12 in 5% dextrose. These results may reduce the workload of clinical staff and minimize drug waste from treatment delays without any loss in product quality and biological activity.